Less Pain with Intra-Articular Hyaluronic Acid Injections for Knee Osteoarthritis Compared to Placebo: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Migliorini, Filippo; Maffulli, Nicola; Schäfer, Luise; Kubach, Joshua; Betsch, Marcel; Pasurka, Mario (Pharmaceuticals, 2024)
The present meta-analysis investigated the efficacy of intra-articular hyaluronic acid (HA) injections for knee osteoarthritis. The outcomes of interest were the visual analogue scale (VAS) and Western Ontario McMaster Osteo-Arthritis Index (WOMAC) scores. This study was conducted according to the 2020 PRISMA statement. All the randomised controlled trials (RCTs) comparing the efficacy of intra-articular HA injections versus placebo injections for knee osteoarthritis were accessed in September 2024. Data from 3851 patients were collected. In total, 64% (2467 of 3851 patients) were women, and the mean age of the patients was 63.5 ± 4.9 years. At baseline, good comparability was found for the mean age, BMI, percentage of women, and patient-reported outcome measures (PROMs). Studies which reported data from two to four weeks of follow-up evidenced a lower value of the subscales pain (p < 0.0001) and stiffness (p = 0.01) of the WOMAC score. No difference was observed in VAS at rest (p = 0.4), VAS at exercise (p = 0.1), and subscale function (p = 0.4) of the WOMAC score. Studies which reported data from five to eight weeks of follow-up evidenced lower VAS at rest in favour of the HA group (p = 0.01). No difference in the other PROMs of interest was observed: VAS at exercise (p = 0.1), and the subscales pain (p = 0.3), function (p = 0.4), and stiffness (p = 0.4) of the WOMAC score. The current level I of evidence suggests that intra-articular HA injections in the knee might reduce pain in the short term.
CRIS-Team Scopus Importer:2024-12-06
Keywords: hyaluronic acid; infiltrations; knee; osteoarthritis; placebo